1999
DOI: 10.1103/physrevlett.82.5124
|View full text |Cite
|
Sign up to set email alerts
|

NonlinearσModel for Inhomogeneous Spin Chains

Abstract: We derive a non-linear σ model (NLSM) generally representing antiferromagnetic Heisenberg spin chains with inhomogeneous spin magnitudes and inhomogeneous nearest-neighbor exchange constants arrayed in finite periods. Only a restriction is that the average of spin magnitudes on one sublattice is the same as that on the other sublattice. The NLSM gives the gapless condition explicitly written by the spin magnitudes and the exchange constants. We apply this gapless condition to several cases including systems wi… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
30
0

Year Published

2000
2000
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(32 citation statements)
references
References 19 publications
2
30
0
Order By: Relevance
“…[10]. Integrating out the fluctuations and taking the continuum limit, we finally obtain the effective action [10]:…”
Section: Nlsm For the General Spin Chainmentioning
confidence: 99%
“…[10]. Integrating out the fluctuations and taking the continuum limit, we finally obtain the effective action [10]:…”
Section: Nlsm For the General Spin Chainmentioning
confidence: 99%
“…Among these studies, the systems with unique spins and different spins in the unit cell have been found to give rise to novel quantum phases and unusual thermodynamic properties. [10][11][12][13][14][15][16][17][18][19][20] It has also been pointed out that the mixture of ferromagnetic and antiferromagnetic interactions 21-23 provides interesting properties. Many such low-dimensional molecular magnetic structures have also been synthesized.…”
mentioning
confidence: 99%
“…The period of the system 2b is regarded as 6 for convenience. After a standard procedure, 29 we have the effective action for the spin-͑1, 1/2, 1/2͒ Hamiltonian,…”
Section: B Haldane-like Gapmentioning
confidence: 99%